Comparison of Sublingual and Vaginal Misoprostol for Cervical Ripening before Curettage: A Randomized Controlled Trial - Sukanya Chamnan; Suttida Intharaburan (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objective:To compare the effectiveness and side effects of misoprostol as a cervical ripening agent through two different routes of administration before curettage.Materials and Methods: The study employed a hospital based prospective randomized controlled trial. A total of 70 patients were simple random divided in two groups for 400 micrograms sublingual and vaginal administration. The drug was administered 6 hours before dilatation and curettage or fractional curettage. Efficacy was assessed on cervical dilatation achieved, pain score and vaginal blood loss. The tolerable limit was noted based on side effects.Results: The sublingual group had significantly more cervical dilatation than the vaginal group (median cervical dilatation 7 mm vs. 5 mm, P < 0.001). Significantly less pain scores (VAS) in sublingual group than vaginal group (3.3 vs. 4.8, P < 0.001). Postoperative vaginal blood loss in the sublingual group was significantly greater than the vaginal group (20 ml vs. 10 ml, P < 0.001). Other side effects such as fever, chill, nausea, vomiting and diarrhea did not differ in both groups.Conclusion: Sublingual misoprostol could be more effective for cervical dilatation, but presents greater postoperative vaginal blood loss than vaginal route.